The Value of Character Education of Transliteration and Translation in Bugis Wisdom of Andi Hasan Machmud - Mukarramah AS.; Syamsudduha Syamsudduha; Andi Fatimah Yunus (Indonesian Journal of Pedagogical and Social Sciences, 2021)
Abstract. The aim of this study is to describe the value of character education of transliteration and translation in Bugis wisdom of Andi hasan Mahmud. Type and design of this study is a description qualitative. The data in this study is written data of an advice that demonstrates the value of character education contained in Bugis transliteration and translation of Andi Hasan Machmud, while the source of the data in this study is Silasa: Setetes Embun di Tanah Gersang by Andi Hasan Machmud. The techniques used to obtain the data in this study include documentation technique, reading technique, and note-writing technique. The technique which was used to analyze the data is miles and Huberman, which consist of data collection, data reduction, data presentation, and a deduction/verification. The study has found eleven forms of value of character education of transliteration and translation in Bugis wisdom of Andi hasan Mahmud those are the value of religious, honesty, tolerance, hard work, democracy. curiosity, appreciative achievement, communicative/friendly, peaceable, social concern, and responsibility.Keywords: Value, Character education and wisdom.